2015
DOI: 10.1016/j.jadohealth.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years After International Conference on Population and Development: Where Are We With Adolescent Sexual and Reproductive Health and Rights?

Abstract: The International Conference on Population and Development in Cairo in 1994 laid out a bold, clear, and comprehensive definition of reproductive health and called for nations to meet the educational and service needs of adolescents to enable them to deal in a positive and responsible way with their sexuality. In the context of the ongoing review of the International Conference on Population and Development Programme of Action and the considerations for a post-2015 development agenda, this article summarizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
155
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(181 citation statements)
references
References 18 publications
7
155
1
9
Order By: Relevance
“…Our study results are similar to that of Bankole et al, (2010) which found that access to sexual and reproductive health services including sexual education was still a challenge, worldwide [13]. A recent review of progress with adolescent sexual and reproductive health over the past twenty years showed a chronic lack of access to sexual and reproductive health information and services [15]. Some other studies have reported similar findings [14, 16, 17].…”
Section: Discussion and Recommendationsupporting
confidence: 90%
“…Our study results are similar to that of Bankole et al, (2010) which found that access to sexual and reproductive health services including sexual education was still a challenge, worldwide [13]. A recent review of progress with adolescent sexual and reproductive health over the past twenty years showed a chronic lack of access to sexual and reproductive health information and services [15]. Some other studies have reported similar findings [14, 16, 17].…”
Section: Discussion and Recommendationsupporting
confidence: 90%
“…Mas, ainda que se considere essa possível limitação, estudos revelam alto nível de desconhecimento dos adolescentes sobre as partes, as funções e mudanças do corpo, sobre menstruação, contracepção e a sexualidade de modo geral. 5,24,25 Retomando as possíveis limitações quanto ao desenho utilizado para a identificação das estruturas dos genitais externos masculino e feminino, cabe ressaltar que os alunos da escola A apresentaram percentual de acerto acima de 75% para todas as estruturas. Além disso, na aplicação do teste-piloto não houve qualquer relato quanto à dificuldade de entendimento do desenho e da associação com a fisiologia de cada estrutura.…”
Section: Discussionunclassified
“…O que a literatura enfatiza é que tanto os professores quanto familiares não se sentem preparados ou capacitados para assumirem o papel de orientadores 7,25 e que é premente a busca por alternativas investigativas e interventivas que deem amplitude às discussões sobre sexualidade com os adolescentes, 25 incluindo abordagens como sexo, geração, violência nas relações de intimidade, direitos sexuais e reprodutivos e acessibilidade aos serviços de saúde e o protagonismo dos adolescentes em sua forma de ser e viver sua sexualidade.…”
unclassified
“…Bu öncelikli gruplardan birisi adölesanlar ve gençlerdir [2,3]. Dünya Sağlık Örgütüne (DSÖ)'ne göre 15-24 yaş arası olarak tanımlanan gençlik dönemi çocukluk ile erişkinlik arasında yaşanan, gencin toplumsal yerini araştırdığı; fiziksel, psikolojik ve sosyal olgunluğa erişmeye çalıştığı uzun ve riskli bir dönemdir [4][5][6][7].…”
Section: Introductionunclassified